Spring Wheat Seeds Different Sowing Methods And Influence On Capsuling Yield Indicators (Texas Journal of Agriculture and Biological Sciences, 2024)
The researches were carried out at the experimental field of the "Shurtanboy" MFY grain and rice scientific production association, Nukus district of the Republic of Karakalpakstan. In this regard, experiments were carried out on different sowing methods and encapsulation of seeds of spring soft wheat resistant to drought and diseases, with high yield and high grain quality, in weak and medium salinity areas of the Republic of Karakalpakstan, especially in the island region.